Risk Factors for Acute Febrile Reaction after Zoledronic Acid Treatment for Primary Osteoporosis - WU Hongliang; ZHENG Sihang; ZHANG Enchong; HOSSAIN Mohammad Showkat; GONG Helong; XING Ruida; JING Shengjie; LI Yan (康复学报)
ObjectiveTo investigate the characteristics and risk factors of acute febrile reaction after zoledronic acid treatment for primary osteoporosis.MethodsA total of 517 patients diagnosed with primary osteoporosis and treated with zoledronic acid from January 2012 to December 2020 were recruited, including 40 males and 477 females, among whom 262 were with type Ⅰ osteoporosis and 255 were with type Ⅱ osteoposis, 245 patients with mild-to-moderate osteoporosis, 272 patients with severe osteoporosis, 230 patients with fresh fracture, and 209 patients with operation. The two groups were compared, and the fever rate and clinical characteristics of fever were summarized and further analyzed in the aspects of gender, age, count of white blood cells, neutrophils, lymphocytes, neutrophil-lymphocyte ratio (NLR), type of osteoporosis, degree of osteoporosis, fracture, surgery intervention, medication history, etc. Multivariate Logistic regression analysis was conducted and ROC curve was drawn to explore the main risk factors for acute febrile reaction.ResultsThe 175 cases (33.85%) developed acute febrile reaction, most of which occurred within 36 hours after treatment, mainly low and moderate fever (<39 ℃), and the duration was generally no more than 60 hours. Univariate analysis showed significant differences in NLR, type and degree of osteoporosis, fresh fracture, surgery intervention, and zoledronic acid medication history between the fever and non-fever groups (P<0.05). There was no significant difference in gender, count of white blood cells, neutrophils and lymphocytes between the two groups (P>0.05). Logistic regression and ROC curve analysis showed that the surgery group had a higher fever rate (P<0.01, area under ROC curve was 0.65). The fracture group had a higher fever rate (P<0.05, area under ROC curve was 0.60). The group with type Ⅰ osteoporosis had a higher fever rate (P<0.01, area under ROC curve was 0.44). The group with medication history had a lower fever rate (P<0.01, area under ROC curve was 0.34). The fever rate of joint fracture group (56.60%) was significantly higher than spine fracture group (38.54%) (P<0.05).ConclusionSurgery, fracture, type Ⅰ osteoporosis and first zoledronic acid medication might be independent risk factors of acute febrile reaction after medication. Patients who had surgery before medication (especially those with joint fracture surgery), fresh fracture, type Ⅰ osteoporosis and first zoledronic acid medication, had a higher risk of acute febrile reaction.